The role of memory ability, depth and mode of recall in the impact of memory on later consumption. (1st June 2020) - Szypula, Joanna; Ahern, Amy; Cheke, Lucy
Abstract: It has been shown that recalling a meal eaten a few hours earlier (vs. the previous day) leads to reduced snacking ('meal-recall' effect). This study attempted to replicate this effect, by assessing participants' (N = 77, mean age = 33.30 [SD = 14.98], mean BMI = 23.77 [SD = 3.72], 74% female) biscuit consumption during a bogus taste test in two separate sessions, before which participants recalled a recent or a distant meal. It was explored whether factors that might affect the quality of a meal-memory, particularly individual differences in memory ability and depth of recall, would influence the meal-recall effect. To this end, only participants with a low or high memory ability were recruited for the study and were allocated to either an unguided-recall or guided-recall condition. In the unguided condition, participants were asked to recall what they ate, and in the guided condition they were prompted for further details regarding their meal. Participants were asked to either recall their meal out loud through an interview with the experimenter or by writing their recollection down on the computer. Contrary to the initial hypotheses, it was found that only the written group demonstrated the meal-recall effect, whereas the verbal group did not. Moreover, this was specific to the written, unguided group, in which participants ate about 9 g fewer biscuits after recalling a recent (vs. a distant) meal, F (1, 15) = 6.07, p  = .026, ηp 2  = 0.288. The written, guided group's snacking seemed to increase by about 8 g after recalling a recent (vs. a distant) meal, F (1, 20) = 7.31, p  = .014, ηp 2  = 0.268. The meal-recall effect was not evident in the verbal group. Memory ability did not influence the magnitude of the meal-recall effect. The results highlight the importance of contextual factors in modulating the meal-recall effect.